2017
DOI: 10.20950/1678-2305.2017v43n2p194
|View full text |Cite
|
Sign up to set email alerts
|

Variações nas capturas das lagostas vermelha (Panulirus meripurpuratus), verde (Panulirus laevicauda Latreille, 1817) e sapata (Scyllarides brasiliensis Rathbun, 1906) na costa de Pernambuco

Abstract: Lobsters are valuable fisheries resources in the northeast coast of Brazil. In the Pernambuco state the catches of the red (Panulirus meripurpuratus) and the green (Panulirus laevicauda) spiny lobsters are high, while the catches of the slipper lobster (Scyllarides brasiliensis) is low. In this study the variability of the monthly and annual catches of those three species were analyzed with data obtained between 1999 and 2006. Overall the red lobster predominates in the catches. Catch of the red and the green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…This may be due to the lack of knowledge of the published work by Giraldes & Smyth (2016). However, some authors have already identified the species with the new taxonomic category (Lima & Andrade 2018, D'oliveira 2017, Ribeiro 2017, Santana et al 2016. Based on the new taxonomic definition, from now on we will consider the Brazilian species P. argus as P. meripurpuratus.…”
Section: Which Is the Spiny Red Lobster Species In Brazil?mentioning
confidence: 99%
“…This may be due to the lack of knowledge of the published work by Giraldes & Smyth (2016). However, some authors have already identified the species with the new taxonomic category (Lima & Andrade 2018, D'oliveira 2017, Ribeiro 2017, Santana et al 2016. Based on the new taxonomic definition, from now on we will consider the Brazilian species P. argus as P. meripurpuratus.…”
Section: Which Is the Spiny Red Lobster Species In Brazil?mentioning
confidence: 99%
“…Historically, research on lobsters in Brazil focuses primarily on their biological parameters (Ivo 2000, Silva et al 2008, Oliveira et al 2015, Giraldes & Smyth 2016, effort control and fishery management (Ivo et al 1995, Carvalho et al 1996, Cavalcante & Furtado-Neto 2012, Santana et al 2015, fishery production (Ivo & Ribeiro-Neto 1996a, Fonteles-Filho 2000, Duarte et al 2010, Ivo et al 2013, Madrid & Izquierdo 2013, Lima & Andrade 2017, and on lobster farming (Igarashi et al 2000, Igarashi 2007. These studies provide key information for the regulation of these lobster fisheries.…”
Section: Introductionmentioning
confidence: 99%
“…No histórico avaliado, o período de defeso ocorreu anualmente entre 1 de janeiro a 30 de abril regulamentado pela Portaria n o 137, de 12 de dezembro de 1994(IBAMA, 1994b). Capturas realizadas por mergulho eram proibidas no referido período, porém eram efetuadas(IBAMA, 2007;ANDRADE, 2017).…”
unclassified